Self-assembly of Ru4 and Ru8 assemblies by coordination using organometallic Ru(II)2 precursors: Synthesis, characterization and properties - Shanmugaraju, Sankarasekaran; Samanta, Dipak; Mukherjee, Partha Sarathi (Beilstein Journal of Organic Chemistry, 2012)
Coordination-driven self-assembly of binuclear half-sandwich p-cymene ruthenium(II) complexes [Ru2(μ-η4-C2O4)(MeOH)2(η6-p-cymene)2](O3SCF3)2 (1a) or [Ru2(μ-η4-N,N'-diphenyloxamidato)(MeOH)2(η6-p-cymene)2](O3SCF3)2 (1b) separately with an imidazole-based tetratopic donor L in methanol affords two tetranuclear metallamacrocycles 2a and 2b, respectively. Conversely, the similar combination of L with 2,5-dihydroxy-1,4-benzoquinonato (dhbq) bridged binuclear complex [Ru2(μ-η4-C6H2O4)(MeOH)2(η6-p-cymene)2](O3SCF3)2 (1c) in 1:2 molar ratio resulted in an octanuclear macrocyclic cage 2c. All the self-assembled macrocycles 2a–2c were isolated as their triflate salts in high yields and were characterized fully by multinuclear (1H, 13C and 19F) NMR, infrared (IR) and electrospray ionization mass spectrometry (ESIMS). In addition, the molecular structure of macrocycle 2a was established unequivocally by single-crystal X-ray diffraction analysis and adopts a tetranuclear rectangular geometry with the dimensions of 5.53 Å × 12.39 Å. Furthermore, the photo- and electrochemical properties of these newly synthesized assemblies have been studied by using UV–vis absorption and cyclic voltammetry analysis.
Keywords: cages; macrocycles; ruthenium(II); self-assembly; self-sorting